Using Mind Mapping Strategy to Improve 8th Graders’ Abilities to Summarize and Retell Stories - Carbiriena Solusia (J-SHMIC : Journal of English for Academic, 2020)
This research aimed at investigating whether or not there were significant differences in summarizing and retelling achievements between the eighth graders who were exposed with Mind Mapping strategy and those who were not. The population was the eighth graders of one of the Junior High Schools in Palembang. Sixty students were taken as the sample and were put into control and experimental groups. Both control and experimental groups were given pre and post tests, but only the experimental group was given the exposure of Mind Mapping strategy. To collect the data, writing and speaking tests were given and then analyzed by using paired sample t-test and independent sample t-test. The results showed that there were significant improvements in the students’ summarizing and retelling achievements in the experimental group after the treatment given. There were also significant improvements in summarizing and retelling achievements between the experimental and control groups.